Micropropagation of kiwi Actinidia chinensis (Baghdad Science Journal, 2007)
Shoot tip of Actinidia chinensis plant were excised and sterilized with mercuric chloride (Hgcl2) at concentration 0.1% for 5 min, then cultured on MS medium supplemented with benzeladinine BA at concentration (0.0,0.5,1.0,2.0,2.5) mg/l in multiplication stage Moreover, indole butyric acid IBA at concentration (0.0, 0.5,1.0,2.0,4.0) mg/l and (0.0,0.5,1.0,2.0) mg/l on solid and liquid solution media respectively in rooting stage were studied. All experiments have done under controlled conditions (25 ±2) Cº and 1000Lux light intensity for 16 hrs / day.Results revealed that supplementing the media with BA at concentrations 2.0 and2.5 mg/l was superior to give highest rate of shoot and number of leaves reached 5.8 /explant and 6.0 leaves respectively. While control treatment gave highest rate of shoot lengths reached 1.99cm Moreover, including liquid media with 2.0 mg/l IBA gave highest rooting percentage(100% )as compared with the same concentration of IBA which gave rooting percentage reached 90% . Results of Acclimatization stage showed that addition of 1:1 peatmos and loamy soil was superior to give highest rate of success( 100%) after 4 weeks of acclimatization .